Environmental Harm and the Political Economy of Consumption - White, R. D. (Social justice, 2002)
Part of a special section on globalization and environmental harm. It is argued that adequate study of environmental harm must stem from sustained analysis of the basic institutions and structures of contemporary capitalism. The centrality of capitalist political economy to the construction of the substantive environmental problem and to the limitations of existing regulatory regimes in relation to this problem is demonstrated. In particular, the relation between production and consumption, the developments underpinning the extension of consumerism in capitalist society, and the symbolic place of consumption and its association with the realization of surplus value by capital are discussed.